Large scale inverse problems computational methods and applications in the earth sciences - Cullen, Michael J. P.; Freitag, Melina A., 1980-; Kindermann, Stefan, 1972-; Scheichl, Robert, 1972- (Radon series on computational and applied mathematics., 2013)
This book is thesecond volume of three volume series recording the ""Radon Special Semester 2011 on Multiscale Simulation & Analysis in Energy and the Environment"" taking place in Linz, Austria, October 3-7, 2011. The volume addresses the common ground in the mathematical and computational procedures required for large-scale inverse problems and data assimilation in forefront applications.